Totalitaryzm w cywilizacji informatycznej - Bäcker, Roman (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The totalitarianism of the information civilisation is, in comparison with the 20th century, much more varied, much more attractive externally and usually less likely to use violence. However, in its essence it does not differ from its predecessor of the industrial era. Its definitional features include political gnosis and the existence of a quasi-charismatic leader as well as, to a lesser extent, the existence of a structure typical of a religious order-like political party.
Keywords: cywilizacja informatyczna; gnoza polityczna; glamour totalitaryzmu